In the Eye of the Beholder: Identity and Nostalgia in Post-Unification German Cinema - Zmarzly, Joshua S. (My University, 2014)
In this study, I wish to examine several films produced in the decades after German Unification (die Wende) to show their relation to themes of identity, historical memory, and nostalgia in the culture of former East Germans. The prevailing subject I seek to research in this context of cinema and historical memory is "Osatalgia"? (German: "ost" [east] + "nostalgie" [nostalgia]), a pop culture movement dedicated to celebrating and reclaiming aspects (usually material) from the East German past.
Keywords: Collective memory and motion pictures--Germany (East); Motion pictures--Germany (East)--History; Motion pictures, German--History; Nostalgia in motion pictures--Germany (East); Ostalgia movement